Potential for waste heat utilization of hot‐water‐cooled data centers: A case study. Issue 5 (26th February 2020) - Oltmanns, Johannes; Sauerwein, David; Dammel, Frank; Stephan, Peter; Kuhn, Christoph
Abstract: The electric energy demand of data centers in Germany has grown rapidly from 10.5 TWh/a in 2010 to 13.2 TWh/a in 2017, an average of 25% of which are used to fulfill the data centers' cooling demand. In order to increase its energy efficiency, TU Darmstadt applies a new cooling concept in the next generation of its high‐performance computing data center "Lichtenberg II." Instead of the current air‐cooled servers with water‐cooled rear doors at 17‐24°C, the new data center will be equipped with direct hot‐water cooling for the high‐performance computer, supplying heat at a temperature of 45°C. The high‐temperature waste heat is used for heating purposes on the university's campus Lichtwiese. For waste heat utilization, two concepts are presented, either integrating the heat in the return line of the district heating network or using it locally in buildings located near the data center. Reductions in CO2 emission and annuity are generated both by decreased compression cooling demand for the data center and by decreased heat generation due to waste heat utilization. Depending on the scenario, a total of 20%‐50% of the waste heat emitted by the high‐performance computer can be used for heating purposes, while the remaining heat is dissipated efficiently via free cooling without additional energy demand for mechanical chillers. CO2 emission can be decreased by up to 720  t CO 2 / a, representing a reduction of about 4% of the total emission at campus Lichtwiese. TU Darmstadt is currently implementing the waste heat integration into its district heating network and will benefit from this concept starting in 2020. Abstract : Although a lot of data centers are located in the vicinity of other buildings with heat demand, most of the emitted waste heat goes unused because its temperature is too low and the operators of the data center and adjacent buildings are not interested in a collaboration. This article shows that connecting water‐cooled servers (supplying an output temperature of 45°C) with the utilization of the waste heat for building heating purposes reduces the data center's demand for cooling energy as well as the building demand for heat from other sources and can therefore be beneficial for both parties.